(untitled) (Revista Contexto & Saúde, 2025)
In recent years, Brazil has emerged as a primary destination for migratory flows driven by political, socioeconomic, and religious factors, receiving refugees from various countries. Ensuring access to food and maintaining adequate nutritional status are central to protection measures. Existing data on the recognition process in the country do not encompass dimensions of health and food. In 2015, Portugal published a Welcoming Manual that addresses rights related to health, food, and nutritional security, serving as a reference for nutritional interventions for refugees in that country. This study translated and adapted the recommendations from this Manual, establishing a dialogue with the Dietary Guidelines for the Brazilian Population from the Ministry of Health. Understanding and recognizing dietary specificities is essential to initiating adequate reception. The translated and adapted dietary recommendations intend to be a guide for nutritional reception and can be regarded as a starting point for health professionals, emphasizing the need for broader discussions and studies to support public policies for reception.